2021
DOI: 10.25311/keskom.vol6.iss3.599
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Rebusan Daun Sirih Merah (Piper Crocatum) Terhadap Penyembuhan Luka Perineum pada Ibu Postpartum di Desa Tanjung Jati Kecamatan Binjai Kabupaten Langkat

Abstract: Proses persalinan hampir 90% yang mengalami robekan perineum, baik dengan atau tanpa episiotomi Angka kejadian robekan perineum terjadi hampir 90 % pada proses persalinan normal. Daun sirih merah atau Piper crocatum diketahui mempunyai kandungan kimia yang berefek antiseptik dan antibakteri. Tujuan penelitian ini adalah menilai lama penyembuhan luka perineum ibu postpartum dengan menggunakan rebusan daun sirih merah dan obat anti septik di Desa Tanjung Jati Kecamatan Binjai Kabupaten Langkat . Metode Penelitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
0
0
1
Order By: Relevance
“…This literature review reviews the Effectiveness of Betel Leaf Water Use on Perineal Wound Healing in post-partum Mothers. The main findings revealed that: (i) Boiled water and soaking water of green and red betel leaves were used as herbal remedies to heal perineal wounds in postpartum mothers; (ii) To heal the perineal wound, intervention is given through washing the perineal wound area, sitting soaking, splattering, and vulva hygiene using betel leaf water; (iii) The use of betel leaf water has been shown to have a significant effect on the healing of perineal wounds in post-partum mothers, can increase the average speed of perineal wound healing, and can reduce the degree of perineal wounds in post-partum mothers(1, 3,6,[8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This literature review reviews the Effectiveness of Betel Leaf Water Use on Perineal Wound Healing in post-partum Mothers. The main findings revealed that: (i) Boiled water and soaking water of green and red betel leaves were used as herbal remedies to heal perineal wounds in postpartum mothers; (ii) To heal the perineal wound, intervention is given through washing the perineal wound area, sitting soaking, splattering, and vulva hygiene using betel leaf water; (iii) The use of betel leaf water has been shown to have a significant effect on the healing of perineal wounds in post-partum mothers, can increase the average speed of perineal wound healing, and can reduce the degree of perineal wounds in post-partum mothers(1, 3,6,[8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency and length of time for intervention varied in each article. Six of the articles mentioned the frequency and duration of intervention, namely 5 and 10 days for 5 to approximately 90 days (3 months) (3,7,8,9,10,11), with two of them providing intervention twice a day for 5 and 7 days (11,7). Then two other articles only mentioned the time the intervention was given, namely 1 and 7 months (1, 6).…”
Section: Effectiveness Of Using Betel Leaf Water For Healing Perineal...mentioning
confidence: 99%
See 1 more Smart Citation
“…Carvakrol is a disinfectant and antifungal so it is used as an antiseptic medicine 13,34 . Red betel leaf extract is able to eat the fungus Candida Albicans which causes acute vaginal discharge, and itching of the genitals, and prevents infection in wounds 22,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Kasus robekan perineum di seluruh dunia terjadi hampir 2,7 juta pada ibu bersalin. Luka robekan perineum episiotomi dengan perawatan luka yang kurang baik serta keadaan lembab yang disebabkan karena adanya pengeluaran lokhea merupakan suatu tempat atau media baik bagi berkembangnya kuman yang menjadi penyebab keadaan infeksi masa nifas (Siagian et al, 2021) Robekan yang terjadi beresiko mengalami infeksi jika kurangnya pengetahuan perawatan perineum, contohnya seperti tidak membersihkan tangan terlebih dahulu terutama sebelum membersihkan alat genetalia, tidak mengeringkan alat genetalia setelah BAK maupun BAB, serta kekeliruan saat melakukan cebok tidak dengan cara yang benar sesuai dengan yang di ajarkan yaitu dari depan ke belakang untuk menjaga kebersihan diri ataupun personal higyene terutama luka perineum serta terjadinya penurunan daya tahan tubuh pada ibu setelah proses persalinan (Gustirini, 2021).…”
Section: Pendahuluanunclassified